The influence of parental education and household financial behavior on halal food consumption in Tanjung Pinang City, Indonesia - Sari, Sella Kurnia; Firdaus, Firdaus; Ningsih, Selly Kudrati; Yonantha, Ferri (Journal of Islamic Economics Lariba, 2026)
IntroductionHalal consumption has become an essential aspect of consumer behavior in Muslim-majority societies, reflecting not only religious compliance but also ethical and quality considerations. While prior studies have emphasized religiosity and awareness as key drivers, limited research has examined how household-level factors, particularly parental education and financial behavior, shape halal food consumption. In urban contexts such as Tanjung Pinang City, understanding these determinants is critical due to the interaction between socio-economic conditions and daily consumption practices.ObjectivesThis study aims to analyze the influence of parental education, household savings, and household expenditure on halal food consumption behavior. It also seeks to explore how educational and financial factors jointly shape household decision-making in the context of halal consumption.MethodThe study employs a quantitative approach using primary data collected from 100 household decision-makers in Tanjung Pinang City. Data were gathered through structured questionnaires using a Likert scale and complemented by interviews. The analysis applies multiple linear regression using the Ordinary Least Squares method to examine the relationships between the independent variables—parental education, savings, and expenditure—and halal food consumption behavior.ResultsThe findings indicate that parental education has a positive and significant effect on halal consumption behavior, suggesting that higher education enhances awareness and adherence to halal principles. Household expenditure also shows a positive relationship, indicating that greater purchasing power facilitates access to halal-certified products. In contrast, household savings exhibit a negative effect, implying that financial caution may limit spending on halal goods. Collectively, these variables explain a substantial proportion of variation in halal consumption behavior.ImplicationsThe results highlight the importance of integrating educational and economic dimensions in promoting halal consumption. Enhancing halal literacy and improving access to affordable halal products are essential for strengthening household compliance with halal principles.Originality/NoveltyThis study contributes to the literature by providing an integrated analysis of parental education and household financial behavior as determinants of halal consumption in a regional urban context, offering new insights into the socio-economic dynamics of Islamic consumer behavior.